Linguistic Activities for Improve Listening and Speaking Skills/ Ø§Ù„Ø£Ù†Ø´Ø·Ø© Ø§Ù„Ù„ØºÙˆÙŠØ© Ù„ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ ÙˆØ§Ù„ÙƒÙ„Ø§Ù… - Chamidah, Dewi; Istiqomah, Rosyida (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Listening and speaking skills are important in learning languages, especially Arabic. A language activity needs to be held to support the student's skills. Linguistic activities are all kinds of activities that are implemented to learn a language. The purpose of this research is to uncover and analyze the appropriate activities and the supporting and inhibiting factors of these activities at